Adeno-Associated Virus-Mediated RNAi against Mutant Alleles Attenuates Abnormal Calvarial Phenotypes in an Apert Syndrome Mouse Model - Fengtao Luo; Yangli Xie; Zuqiang Wang; Junlan Huang; Qiaoyan Tan; Xianding Sun; Fangfang Li; Can Li; Mi Liu; Dali Zhang; Meng Xu; Nan Su; et al. (Elsevier, 2018)
Apert syndrome (AS), the most severe form of craniosynostosis, is caused by missense mutations including Pro253Arg(P253R) of fibroblast growth factor receptor 2 (FGFR2), which leads to enhanced FGF/FGFR2-signaling activity. Surgical correction of the deformed skull is the typical treatment for AS. Because of constant maldevelopment of sutures, the corrective surgery is often executed several times, resulting in increased patient challenge and complications. Biological therapies targeting the signaling of mutant FGFR2 allele, in combination with surgery, may bring better outcome. Here we screened and found a small interfering RNA (siRNA) specifically targeting the Fgfr2-P253R allele, and we revealed that it inhibited osteoblastic differentiation and matrix mineralization by reducing the signaling of ERK1/2 and P38 in cultured primary calvarial cells and calvarial explants from Apert mice (Fgfr2+/P253R). Furthermore, AAV9 carrying short hairpin RNA (shRNA) (AAV9-Fgfr2-shRNA) against mutant Fgfr2 was delivered to the skulls of AS mice. Results demonstrate that AAV9-Fgfr2-shRNA attenuated the premature closure of coronal suture and the decreased calvarial bone volume of AS mice. Our study provides a novel practical biological approach, which will, in combination with other therapies, including surgeries, help treat patients with AS while providing experimental clues for the biological therapies of other genetic skeletal diseases. Keywords: craniosynostosis, Apert syndrome, Fgfr2, adeno-associated virus, RNAi, molecular therapy